Negotiating between the accountability and the innovation mandates: evidence from Italian schools - Laura Mentini (Taylor & Francis Group, 2024)
In Italy, the National Evaluation System (SNV), encompassing both internal and external accountability components, is designed not only to hold school actors accountable but also to stimulate innovation and change in pedagogical practices. Nevertheless, existing literature presents inconclusive and contradictory findings regarding the effects and the relationship between school performance-based accountability (PBA) and educational innovation. Utilizing sensemaking and filtering theories, this paper analyses the negotiation of PBA and innovation mandates in Italian schools, emphasizing how school actors interpret, filter, and adapt the policy expectations to their organizational and educational practices. Special attention is given to the influence of local school contexts and performative pressures on this process. The primary data collection method involves interviews with school leadership teams and teachers analysed through an ideal type case analysis. Findings reveal diverse school responses to the double mandates of PBA and innovation. Varied logics of school enactment within the contemporary policy context are identified, influenced by teacher attitudes towards PBA and schools' socio-economic conditions. Innovation is evident in both advantaged and disadvantaged school contexts, albeit with distinct applications and interpretations. Overall, the adaptation of PBA prerogatives in schools to foster innovation and change is neither uniform nor direct, although external pressures impact educational practices across contexts. Beyond socio-economic factors and administrative and marketing accountability pressures, additional intervening elements include school leadership and staff cohesion as well as school infrastructure and material resources.